Survey of integrated flexible job shop scheduling problems. (December 2022) - Li, Xixing; Guo, Xing; Tang, Hongtao; Wu, Rui; Wang, Lei; Pang, Shibao; Liu, Zhengchao; Xu, Wenxiang; Li, Xin
Highlights: 140 related articles of integrated flexible job shop scheduling problems have been analyzed. Five different integration models of the flexible job shop scheduling problems are explained. Future research challenges and directions that can be attempted are demonstrated in Industry 4.0. Abstract: The flexible job shop scheduling problems (FJSP) has been studied for many years, and many different mathematical models and solution approaches have been developed. With the proposal and implementation of Industry 4.0, more focus has been on the integrated optimization of the FJSP to enhance its practicality. However, few reviews on the integrated optimization of the FJSP have been reported. To grasp the current development trend of the integrated FJSP (I-FJSP), this paper presents a comprehensive literature review of the I-FJSP and its extensions. In this context, 140 related articles were collected and analyzed. First, the mathematical model of the FJSP and the overview framework are presented. Subsequently, five different integration models of the FJSP are explained and corresponding qualitative analyses are conducted. Finally, research challenges and directions that can be attempted are demonstrated. We expected that this study will aid academic researchers and application engineers in developing a more comprehensive collision of ideas among each other in Industry 4.0.